Forecasting threats to the Baltic sea region cooperation security in the period of Lithuania integrating into NATO and the EU - Makštutis, Antanas (Journal of Business Economics and Management, 2004)
The work deals with the global economic factors of the world that have an impact on the development of the country's economy and national market as well as on the regional cooperation security under the conditions of Lithuania's integration into NATO and the European Union (EU). Methodological principles of research of internal threats of the regional cooperation security, methodics and methods of their implementation are provided. Forecast is made of the tendencies of human activity efficiency in dependence upon which a description is given of the human life quality and the rational use of resources, the GDP changes and tendencies of competitiveness in the national, EU and world markets. The internal environment for the regional cooperation security in time and space is modelled.First Published Online: 14 Oct 2010